2004
DOI: 10.1001/jama.291.24.2978
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lifestyle Changes on Erectile Dysfunction in Obese Men

Abstract: Context Healthy lifestyle factors are associated with maintenance of erectile function in men.Objective To determine the effect of weight loss and increased physical activity on erectile and endothelial functions in obese men.Design, Setting, and Patients Randomized, single-blind trial of 110 obese men (body mass index Ն30) aged 35 to 55 years, without diabetes, hypertension, or hyperlipidemia, who had erectile dysfunction that was determined by having a score of 21 or less on the International Index of Erecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
517
2
33

Year Published

2006
2006
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 780 publications
(581 citation statements)
references
References 29 publications
22
517
2
33
Order By: Relevance
“…13 It is evident that obese men have a higher incidence of ED affecting their sexual life. 20 Esposito et al 21 found that loss of 10% or more total body weight by reducing calorie intake and increasing levels of physical activity had a higher rate of weight loss and improvement in ED than in controls. Because OSAS is often seen in obese patients, the risk of ED is frequent in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…13 It is evident that obese men have a higher incidence of ED affecting their sexual life. 20 Esposito et al 21 found that loss of 10% or more total body weight by reducing calorie intake and increasing levels of physical activity had a higher rate of weight loss and improvement in ED than in controls. Because OSAS is often seen in obese patients, the risk of ED is frequent in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…24 However not many population-based epidemiological studies measured BMI, and for those that did, the study focus was usually obesity not underweight. Our results show that the ED risk in underweight (OR ¼ 2.99) individuals were comparable and possibly higher than those who were obese (OR ¼ 2.47) among men with no exercise.…”
Section: Discussionmentioning
confidence: 99%
“…12 In 110 obese men without diabetes, hypertension or dyslipidemia, ED was strongly correlated with waist/hip ratio and was significantly improved with weight loss and increased activity, which lowered glucose, insulin, waist/hip ratio, blood pressure and triglycerides, and increased endothelial NO production. 13 In obese men, increased insulin sensitivity, induced by diet and vigorous activity and reflected by reduced circulating insulin, was very strongly correlated with increased NO production (r ¼ 0.83). 14 …”
Section: Weight Lossmentioning
confidence: 95%